Effectiveness of Infographics as a Communication Tool in the Era of Digital Immersion: A Perception Study of Mass Communication Students - Dr. Tanushri Mukherjee, Mr. Rajesh Sharma (International Journal of Advanced Science and Technology, 2020)
In the present times when everything which is visually appealing attracts the attention of the masses, infographics with its very appealing format of visual representation of all kinds of information plays a major role. Its role is visible in the many ways we inform, educate and make people aware in the present times. It gives meaning to many situations which where earlier unexplored or complex in nature to be explained. The visual nature of infographics is an aid to comprehension resulting in better and faster communication and understanding. Messages conveyed through Infographics have a deep imprint in our mind and are also easy to recall, making it a great tool being widely used in classroom teaching methods as well. Through effective application of Infographics as a teaching pedagogy, the teachers can put information in a garb that is visually attractive and memorable and students find such information easy to assimilate and internalize.  Infographics can be both static and interactive with the latter being more appealing. The purpose of the study is to explore the various facets of the effective role of infographics as a major communication tool among the students and to study the reasons behind it being successful in creating a strong impact on the understanding level and interpretation of learners. To achieve the objectives and further substantiate the study, the paper seeks the opinion of  Journalism Students who are taught about the various  contemporary technological tools as a part of their course content and who are aware about the growing significance of  infographics as a major tool of disseminating information and learning in a visually convincing manner.  The paper identifies the perspective of the students regarding the various dimensions of the application of Infographics in today’s world of visual communication. The findings will contribute to focus and formalize plans and future strategies to create and implement more rigorous usage of infographics as a digital communication  tool in the areas most preferred by the sample respondents.